The Definitive Guide to PC-BSD - Lavigne, Dru.; SpringerLink (Online service) (Berkeley, CA : Apress, 2010)
This book is the ultimate reference for both beginners and power users to PC-BSD$1 (Bthe free, easy-to-use operating system based on FreeBSD. Existing power users will learn how to look under the hood and contribute to the global PC-BSD community. PC-BSD is turning into a hassle-free alternative to Linux on the desktop. Enjoy secure, virus-free computing Quickly become a power users
Getting Started with PC-BSD -- Introducing PC-BSD -- Installing PC-BSD -- Using the PC-BSD Desktop -- Customizing the Desktop -- Getting Around -- Performing Common Tasks -- User System Settings -- Administrative System Settings -- Software -- Push Button Installer System -- FreeBSD Packages -- FreeBSD Ports -- Community -- Getting Help -- Getting Involved -- Going Beyond the Basics -- Advanced Tasks -- Becoming a Developer.
Keywords: Computer science; Computer Science; Programming Techniques